Analisis Efektivitas Promosi Lembaga Amil Zakat Dalam Penghimpunan Zakat Bagi Peningkatan Kesejahteraan Keluarga Dhuafa (Studi Kasus Lembaga Amil Zakat Dompet Dhuafa Republika) - Didin Hafidhuddin (Media Gizi dan Keluarga, 2006)
This paper attempted to analyze the effectiveness of promotion towards the collection of Zakah fund in the process of improving poor family welfare by taking case study of Dompet Dhuafa Republika, a nationwide zakah agency. Data were collected from 100 respondents who were the Zakah payers living in the Jakarta, Depok, Bogor, Tangerang, and Bekasi region. EPIC model and Direct Rating Method tests were conducted to examine the promotion's effectiveness. Descriptive statistic and average tests were also used as analytical tools. The results showed that the respondents perceived and believed that Zakah, infaq, and sadaqah could be used as an instrument of poverty alleviation as well as empowerment of poor families. This can be achieved when Zakah, infaq, and sadaqah are managed by trustable and professional institution. The results also showed that the promotions of Dompet Dhuafa Republike were found to be effective.